Pengembangan Model PBL Terintegrasi Kognitif Moral Pada Mahasiswa PGSD UNIPA Surabaya - Danang Prastyo; Dwi Retnani Srinarwati (Universitas Mathla'ul Anwar Banten, 2021)
The research aims to produce learning tools for Moral Cognitive Integrated PBL Learning Model, knowing the level of moral cognitive of PGSD Unipa Surabaya students and the influence of Moral Cognitive Integrated PBL Learning Model on Moral Cognitive of PGSD Unipa Surabaya Students. This type of research is R&D development research that has been simplified into three stages, namely preliminary studies, model development and model validation. The study population was all students of PGSD Class 2020 which consisted of seven classes, namely classes A-F. Whereas the sample of this study were students of PGSD Class 2020 Class A and Class F. The results of the study were the validation results of two validators related to the Cognitive Integrated PBL Learning Model which is very good and feasible to be applied in learning. The fourth level of cognitive morality of PGSD Unipa Surabaya students is oriented towards authority and social care. There are differences in cognitive morals between students who apply Moral Cognitive Based PBL Learning Model and students and students who do not apply Moral Cognitive Based PBL Learning